2000
DOI: 10.1007/s005350070006
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of three-dimensional intraductal ultrasonography in the assessment of longitudinal spread of extrahepatic bile duct carcinoma

Abstract: We investigated the utility and limitations of three-dimensional intraductal ultrasonography (3D-IDUS), for the assessment of the extent of longitudinal cancer spread to the hepatic side by extrahepatic bile duct carcinoma. In eight patients with extrahepatic bile duct carcinoma. 3D-IDUS was used to assess longitudinal cancer extension to the hepatic side prior to resection. When the linear dimension of 3D-IDUS showed bile duct wall thickening that was connected to the tumor and which became thin at a point, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Endoscopic ultrasonography is reported to have sensitivity in detecting bile duct stones >90% and specificity >95% [52]. Similar values are reported for intraoperative and intraductal ultrasonography [53,54,55,56,57,58,59,60]. Magnetic resonance cholangiopancreatography is the only non-invasive technique with very high values of sensitivity and specificity, but it still remains of limited availability in many institutions and of considerable cost.…”
Section: Choledocholithiasismentioning
confidence: 53%
“…Endoscopic ultrasonography is reported to have sensitivity in detecting bile duct stones >90% and specificity >95% [52]. Similar values are reported for intraoperative and intraductal ultrasonography [53,54,55,56,57,58,59,60]. Magnetic resonance cholangiopancreatography is the only non-invasive technique with very high values of sensitivity and specificity, but it still remains of limited availability in many institutions and of considerable cost.…”
Section: Choledocholithiasismentioning
confidence: 53%
“…It allows the reconstruction of acquired data as a multiplanar display or as a 3-D view, which facilitates easier recognition of cancer spread along the bile duct and the configuration of the tumour and the surrounding structures than what is possible with only cross-sectional two-dimensional (2-D) views. Preliminary data on 3-D IDUS have been reported [46][47][48]. Three-dimensional IDUS requires a thick sheath catheter, over three mm in diameter, to achieve smooth movement of the transducer mounted inside during data acquisition.…”
Section: Bile Duct Cancermentioning
confidence: 99%
“…As mentioned above, the longitudinal spread of the bile duct cancer from the main tumour is visualised by IDUS as an irregular and asymmetric thickening of the wall. It is necessary to perform IDUS before establishing biliary drainage as it causes thickening of the bile duct wall, which mimics cancer extension [28, 31,32,45] Although the number of patients included was small, Tamada et al [48] reported the accuracy of IDUS in the evaluation of longitudinal spread of bile duct cancer to be only 50% (four out of eight cases), even with 3-D imaging. Noda et al [45] carried out a comparative study of preoperative IDUS with histological findings in surgical cases with bile duct cancer.…”
Section: Bile Duct Cancermentioning
confidence: 99%
“…Although we expected that IDUS could distinguish cancer infiltration from fibrosis, this determination was difficult. Similarly, Tamada et al 13 have reported difficulty in distinguishing bile duct wall thickening due to cancer spread from that secondary to intlammation, using IDUS and 3D-IDUS.…”
mentioning
confidence: 99%